Olmesartan Associated Enteropathy, an easily overlooked etiology of bowel disturbance: report of three cases (Bangladesh Critical Care Journal, 2022)
Olmesartan medoxomil is one of eight marketed Angiotensin II Receptor Blocker for the treatment of high blood pressure. Olmesartan Associated Enteropathy has been described in several case reports, subsequently, the United states Food and Drug Administrationincluded severe sprue-like enteropathy as an adverse effect of Olmesartan. Olmesartan Associated Enteropathy mimics celiac disease clinically and pathologically. The pathologic findings are villous atrophy and increased intraepithelial lymphocytes. Clinical presentation of Olmesartan Associated Enteropathy includes nausea, bloating, diarrhea and weight loss. In contrast to celiac disease, tissue transglutaminase is not elevated, and there is no response to a gluten-free diet. Several case reports have described the effects of olmesartan on gut, giving rise to the term of Olmesartan Associated Enteropathy. Clinicians should always be aware that Olmesartan can cause an enteropathy clinically and histologically similar to celiac disease since replacing Olmesartan with an alternative antihypertensive drug can simplify the diagnostic workup and provide both clinical and histologic improvement. We report three cases of Olmesartan Associated Enteropathy in this article.Bangladesh Crit Care J September 2022; 10(2): 154-157